2017
DOI: 10.1525/collabra.95
|View full text |Cite
|
Sign up to set email alerts
|

How Much Group is Necessary? Group-To-Individual Transfer in Estimation Tasks

Abstract: Hardt G-I transfer denotes an increase in individual performance due to group interaction, for example, because of acquiring certain skills or knowledge from the other group members. Whereas such G-I transfer has been successfully shown for problem-solving tasks, evidence for G-I transfer on quantitative estimation tasks is scarce. We address this research gap with a focus on how often a group has to interact in order to fully exploit the benefit of this learning effect. Results from two experiments support th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 32 publications
(66 reference statements)
5
24
0
Order By: Relevance
“…It is therefore not unreasonable to assume that the social support for one's views is carried over and amplified in MTM contexts. On the other hand, in a recent empirical study using estimation tasks, individuals improved their performance after a single exposure to the group (Stern et al, 2017) and, in line with this evidence, we would expect that MTM is actually taxing on the confidence of the individuals in their own judgments. We, therefore, formulate the last hypothesis concerning the impact of MTM on changes in confidence as a set of competing claims.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 70%
See 2 more Smart Citations
“…It is therefore not unreasonable to assume that the social support for one's views is carried over and amplified in MTM contexts. On the other hand, in a recent empirical study using estimation tasks, individuals improved their performance after a single exposure to the group (Stern et al, 2017) and, in line with this evidence, we would expect that MTM is actually taxing on the confidence of the individuals in their own judgments. We, therefore, formulate the last hypothesis concerning the impact of MTM on changes in confidence as a set of competing claims.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 70%
“…Such a fostering effect for individual learning is likely to be a reflection of the G-I transfer of learning. Therefore, we build on the G-I transfer of learning (Brodbeck and Greitemeyer, 2000) to argue that individual members use the other group members as information sources and during the group discussion they develop more accurate insights into the estimation tasks and, as a consequence, they improve their individual performance (Stern et al, 2017). In line with this model, if individuals are exposed to more groups, they have access to broader cognitive resources, to more meta-cognitive strategies for dealing with the task, and therefore the G-I transfer of learning is fostered in MTM contexts.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, groups benefit from discussion beyond the aggregation of their members’ judgments. There is mounting evidence that group judgments are more accurate than the simple average of a comparable number of individual judgments, that is, group interaction leads to synergy in quantitative group judgment (e.g., Minson, Mueller, & Larrick, 2018; Schultze, Mojzisch, & Schulz-Hardt, 2012; Sniezek & Henry, 1989; Stern, Schultze, & Schulz-Hardt, 2017). Recent research suggests that the main process driving the superiority of group judgments is group-to-individual transfer (G-I transfer), a group-specific learning effect that denotes increases in group members’ individual accuracy due to exchanging task relevant information during discussion (Schultze et al, 2012; Stern et al, 2017).…”
mentioning
confidence: 99%
“…To the best of our knowledge, only one previous study investigated G-I transfer with regard to mapping and metric knowledge (Stern et al, 2017). The results of this study showed that group members improved their metric knowledge during discussion, but found no evidence of improvements in mapping knowledge.…”
mentioning
confidence: 99%